A comparison of verbal skill and cognitive performance of children having high educated versus low educated parents in urban and rural context - Sarkar, Ratan Kumar (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2010.